Evaluating the effect of Medicaid expansion on access to preventive reproductive care for women in Oregon - Gibbs, Susannah; Harvey, S. Marie; Bui, Linh; Oakley, Lisa; Luck, Jeff; Yoon, Jangho (Preventive medicine, 2020)
We evaluated the effect of the Affordable Care Act (ACA) Medicaid expansion on receipt of preventive reproductive services for women in Oregon. First, we compared service receipt among continuing Medicaid enrollees pre- and post-ACA. We then compared receipt among new post-ACA Medicaid enrollees to receipt by continuing enrollees after ACA implementation. Using Medicaid enrollment and claims data, we identified well-woman visits, contraceptive counseling, contraceptive services, sexually transmitted infection (STI) screening, and cervical cancer screening among women ages 15–44 in years when not pregnant. For pre-ACA enrollees, we assessed pre-ACA receipt in 2011–2013 (n = 83,719) and post-ACA receipt in 2014–2016 (n = 103,225). For post-ACA enrollees we similarly assessed post-ACA service receipt (n = 73,945) and compared this to service receipt by pre-ACA enrollees during 2014–2016. We estimated logistic regression models to compare service receipt over time and between enrollment groups. Among pre-ACA enrollees we found lower receipt of all services post-ACA. Adjusted declines ranged from 7.0 percentage points (95% CI: −7.5, −6.4) for cervical cancer screening to 0.4 percentage points [−0.6, −0.2] for STI screening. In 2014–2016, post-ACA enrollees differed significantly from pre-ACA enrollees in receipt of all services, but all differences were <2 percentage points. Despite small declines in receipt of several preventive reproductive services among prior enrollees, the ACA resulted in Medicaid financing of these services for a large number of newly enrolled low-income women in Oregon, which may eventually lead to population-level improvements in reproductive health. These findings among women in Oregon could inform Medicaid coverage efforts in other states. •Preventive services were compared pre- vs. post-ACA for women on Medicaid.•Service utilization was similar for continuing and new Medicaid enrollees.•Receipt of services declined slightly post-ACA for non-expansion Medicaid enrollees.